Corporate giving in the health sector: a study on the Malaysian companies - Hossain , Dewan Mahboob; Mohamad Diah, Nurazzura (medi+WORLD Internationa, 2015)
Corporate giving represents the philanthropic activities that companies perform as voluntary initiatives. All over the world, companies are contributing in several sectors like health, sports, education and others. In many ways, these activities help in mitigating the social problems and meeting the necessities. This research is based on this issues. The main objective of this research is to examine the nature of contribution of the Malaysian companies in the health sector. In order to achive this objective, the research conducted content analysis of the annual reports of 200 samples companies selected through random sampling. In most of the cases companies disclose their yearlong activities in the annual reports. from these reports the researchers identified the main activities that the companies have performed in order to help the health sector.